Review of research on safety control of seismic wave and shock wave induced by underwater blasting. Issue 3 (4th May 2017) - Peng, Yaxiong; Wu, Li; Su, Ying; Zhu, Binbin; Chen, Chunhui; Li, Bo
Abstract: The safety control methods and indexes of seismic wave and shock wave induced by underwater blasting are, respectively, elaborated in this paper. The single-factor and the double-factor safety control taking both vibration velocity and vibration frequency into consideration are comprehensively analyzed, and the weaknesses of the application scopes of both criteria in the safety performance evaluation of blasting vibration are discussed. Relative researches on the duration time of blasting are introduced, and the duration time for blasting is proposed to be embraced in the scope of safety control. Besides, the research progresses of safety control of water shock wave and aerial shock wave are, respectively, introduced, and the weaknesses of the above methods in the application to underwater blasting engineering are analyzed. Based on the analysis of the adverse effects of seismic wave and shock wave, the new idea to study the synergistic effects of both kinds of waves is put forward, and the comprehensive safety control method which includes both seismic wave and shock wave remains to be developed.